Novel Risk Loci for Rheumatoid Arthritis in Han Chinese and Congruence With Risk Variants in Europeans. Issue 5 (May 2014) - Jiang, Lei; Yin, Jian; Ye, Lingying; Yang, Jian; Hemani, Gibran; Liu, Ai‐jun; Zou, Hejian; He, Dongyi; Sun, Lingyun; Zeng, Xiaofeng; Li, Zhanguo; Zheng, Yi; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate differences in genetic risk factors for rheumatoid arthritis (RA) in Han Chinese as compared with Europeans. Methods A genome‐wide association study was conducted in China with 952 patients and 943 controls, and 32 variants were followed up in 2, 132 patients and 2, 553 controls. A transpopulation meta‐analysis with results from a large European RA study was also performed to compare the genetic architecture across the 2 ethnic remote populations. Results Three non–major histocompatibility complex (non‐MHC) loci were identified at the genome‐wide significance level, the effect sizes of which were larger in anti–citrullinated protein antibody (ACPA)–positive patients than in ACPA‐negative patients. These included 2 novel variants, rs12617656, located in an intron of DPP4 (odds ratio [OR] 1.56, P = 1.6 × 10−21), and rs12379034, located in the coding region of CDK5RAP2 (OR 1.49, P = 1.1 × 10−16), as well as a variant at the known CCR6 locus, rs1854853 (OR 0.71, P = 6.5 × 10−15). The analysis of ACPA‐positive patients versus ACPA‐negative patients revealed that rs12617656 at the DPP4 locus showed a strong interaction effect with ACPAs (P = 5.3 × 10−18), and such an interaction was also observed for rs7748270 at the MHC locus (P = 5.9 × 10−8). The transpopulation meta‐analysis showed genome‐wide overlap and enrichment in association signals across the 2 populations, as confirmed by prediction analysis. Conclusion This study has expanded the list of alleles that confer risk of RA, provided new insight into the pathogenesis of RA, and added empirical evidence to the emerging polygenic nature of complex trait variation driven by common genetic variants.